The varied clinical and radiological manifestations of contrast-induced encephalopathy following coronary angiography - Willman, Josie; Ruuskanen, Jori O; Hassan M; Mustonen, Jussi M; Leppänen; Jaakko; Lähteenoja; Markus; Sipilä Jussi (Taylor & Francis, 2025)
Contrast-induced encephalopathy (CIE) is a rare complication of imaging using ionidated contrast media. Its pathogenesis remains unknown, and its clinical presentation is variable. We present two cases of CIE following coronary angiography (CAG) that underscore the multitude of clinical manifestations and imaging findings associated with the disorder. In patients 1, CIE manifested during the CAG with agitation and decreased consciousness, followed by left hemiparesis and visual neglect. Native computed tomography (CT) of the head was unremarkable but CT perfusion (CTP) showed extensive hypoperfusion of the right hemisphere with corresponding slow-wave activity in the electroencephalogram (EEG). These findings were more pronounced the next day. Magnetic Resonance Imaging (MRI) revealed multiple small dot-like ischemic lesions across the brain. By day six she had fully recovered. Patient 2 developed transient expressive aphasia during the CAG followed by migraineous symptoms. Native head CT showed a large area of parenchymal edema, sulcal effacement and variable subarachnoid hyperdensity in the right hemisphere. He developed mild left side hemiparesis, spontaneous gaze deviation and inattention. Brain MRI showed small dot-like acute ischemic lesions across the brain. The next morning, he had a generalized tonic-clonic seizure (GTCS) after which native head CT was normal, but the EEG showed a post-ictal finding covering the right hemisphere. His hemiparesis resolved within two months. The diversity in clinical and radiographic presentations suggest that CIE involve many pathophysiological processes.